(untitled) (Scientific journal of the Fergana State University, 2023)
This article entails imitative expressions to sound and state in national linguistic view of the world, agglutinative languages, particularly, wide usage of imitations in Uzbek, flektiv languages, additionally, almost non-existence of imitations as an independent part of speech expressing imitation to sound and state with nouns, adjectives or verbs, derivation of imitation with the above words.